Genocias ir rezistencija Nr. 33(1) - Tininis, Vytautas; Bagušauskas , Juozapas Romualdas; Veilentienė, Audronė; Mikelevičius , Laimis; Burinskaitė, kr; ere, Gintautas (Genocidas ir rezistencija, 2013)
Pilnas leidinys